Modulation of Circadian Rhythm of DNA Synthesis in Tumor Cells by Inhibiting Platelet-Derived Growth Factor Signaling - Hiroo Nakagawa; Satoru Koyanagi; Yukako Kuramoto; Akiko Yoshizumi; Naoya Matsunaga; Hiroshi Shimeno; Shinji Soeda; Shigehiro Ohdo (Elsevier, 2008)
Circadian synchronization of cell proliferation is observed not only in normal healthy tissues but also in malignant solid tumors. However, the proliferation rhythm of tumor cells is often different from that of normal cells. We reported here that the peculiar rhythm of tumor cell proliferation was modulated by inhibition of platelet-derived growth factor (PDGF) signaling. DNA synthesis in tumor cells implanted in mice showed a 24-h oscillation apparently differing from that of normal bone marrow cells. Continuous administration of AG1295 (10 μg/h, s.c.), a PDGF receptor tyrosine kinase inhibitor, substantially suppressed DNA synthesis in the implanted tumor cells but not in the healthy bone marrow cells. During the administration of this drug, the rhythm of DNA synthesis in the tumor cells was synchronized with that in bone marrow cells. The present results suggest that the circadian rhythm of DNA synthesis in tumor cells is modulated by PDGF receptor signaling, which is activated following tumor progression. Because the rhythmic patterns of clock gene expression in tumor cells did not differ significantly from those in other healthy tissues, the enhanced signal transduction of PDGF receptor may cause an alteration in the rhythmicity of tumor cell proliferation without changing in the intracellular molecular clockwork. Keywords:: platelet-derived growth factor (PDGF), tumor progression, DNA synthesis, circadian rhythm, clock gene